Mathematical Model Analysis of the Profit-Sharing System in Islamic Banking - Nurhikmah; Ibnu Imam Al Ayyubi; Syed Muhammad Adib Termizi b Ahmad al-Jafari; Fatimatul Mardiah Azzahra; Nurul Afifah Azzahra; Syahrul Ridwan (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
This study examines the transformation of the profit-sharing system in Islamic banking through the application of mathematical models and digital technology. Profit sharing is a fundamental principle in Islamic finance that emphasizes justice, transparency, and blessings in financial transactions; however, its practical implementation often encounters challenges related to complex calculations and limited technological support. Therefore, this study aims to analyze how mathematical models and digital technologies can enhance the effectiveness and transparency of profit-sharing mechanisms in Islamic banking. This research employs a qualitative approach using a literature review and document analysis to examine relevant theories, previous studies, and current practices. The findings indicate that the application of mathematical models improves the accuracy of profit distribution calculations and supports more efficient decision making processes. Furthermore, the integration of digital technologies, such as blockchain and big data, significantly enhances transparency, strengthens public trust, and expands financial inclusion, particularly for communities in remote areas. Nevertheless, issues related to data security, digital literacy, and Sharia compliance remain key challenges. Overall, this study concludes that the synergy between mathematical approaches and digital technology plays a crucial role in strengthening a sustainable, transparent, and equitable Islamic financing system aligned with the objectives of Sharia (maqashid shariah).